PENDAMPINGAN PENGEMBANGAN POTENSI PERTANIAN DI DESA PLOSOSARI KABUPATEN PASURUAN - Fibrianingtyas, Alia; ‘Ula, Mahfudlotul; Amalia, Rizka (Yayasan Education and Social Center, 2024)
Plososari Village in Grati Subdistrict, Pasuruan Regency has abundant natural resources, especially in cassava production. Cassava grows well on the community's farmland, resulting in an abundant harvest every year. However, although the potential of cassava in this village is huge, its utilization is still far from optimal. Most people only sell cassava in its raw form at a relatively low price, so its economic value has not been fully maximized. Nevertheless, the community in this village has sufficient ability and skills to process cassava into more valuable products, such as chips, samiler, or other processed products that have a higher selling value. However, limited access to knowledge about cassava processing and marketing strategies is one of the main challenges faced. Therefore, this activity aims to increase the added value of cassava products through training in innovative packaging design and marketing strategy development. With the hope that it can positively impact the economic welfare of the village community